The buildup of strongly barred galaxies in the TNG100 simulation - Rosas-Guevara, Yetli; Bonoli, Silvia; Dotti, Massimo; Zana, Tommaso; Nelson, Dylan; Pillepich, Annalisa; Ho, Luis C; Izquierdo-Villalba, David; Hernquist, Lars; Pakmor, Rüdiger (Monthly notices of the Royal Astronomical Society, 2020)
We analyse the properties of strongly barred disc galaxies using the TNG100 simulation, a cosmological hydrodynamical realization of the IllustrisTNG suite. We identify 270 disc galaxies at z = 0 in the stellar mass range $M_{*}=10^{10.4-11}\, {\rm M_{\odot }}$, of which 40 per cent are barred. Of the detected bars, more than half are strong. We find that the fraction of barred galaxies increases with stellar mass, in agreement with observational results. Strongly barred galaxies exhibit, overall, lower gas-to-stellar mass ratios compared to unbarred galaxies. The majority of barred galaxies are quenched (sSFR ∼ 10−11.7 yr−1), whereas unbarred galaxies continue to be active (sSFR ∼ 10−10.3 yr−1) on the main sequence of star-forming galaxies. We explore the evolution of strongly barred and unbarred galaxies to investigate their formation and quenching histories. We find that strong bars form between 0.5 < z < 1.5, with more massive galaxies hosting older bars. Strong bars form in galaxies with an early-established prominent disc component, undergoing periods of enhanced star formation and black hole accretion, possibly assisted by cosmological inflows. Unbarred galaxies, on the other hand, assemble most of their mass and disc component at late times. The nuclear region of strongly barred galaxies quenches shortly after bar formation, while unbarred galaxies remain active across time. Our findings are indicative of bar quenching, possibly assisted by nuclear feedback processes. We conclude that the cosmological environment, together with small-scale feedback processes, determine the chances of a galaxy to form a bar and to rapidly quench its central region.